The Impact of Bilingual Class Program on Students’ Speaking Ability - Agustian Agustian; Iis Sujarwati (Universitas PGRI Semarang, 2023)
Abstract. The implementation of a bilingual class program in schools is expected to improve students’ ability to use English. This study examines how bilingual class affects students' English-speaking abilities.This study's goal was to investigate how a bilingual program affected students' capacity to speak more fluently in class XI of Pondok Pesantren Darussalam Kepahiang, Bengkulu. In this research employs a posteriori approach. The survey population consisted of all Class XI students of Pesantren Darussalam Kepahiang. Random sampling was used by researchers to obtain research data. The total number of samples in this study is 35 students from Class XI. A Likert scale questionnaire and a photo-oral test were used as survey tools. To support the study, the researchers used questionnaires as a reference to assess the effectiveness of the bilingual program and oral tests to assess the students' language abilities. Researchers have used regression analysis to analyze existing data. According to results of the study, it was found that Bilingual program had an impact on the speaking ability of the students of Class XI of Pesantren Darussalam Kepahiang. After processing the data, a significant improvement was obtained. In the standard F-table, df = 33 has a significance of 5%, the result is 4.17, and the number of F characters is 113.451. This display that the calculated F value is greater than the F table. It means that students’ English language skills improve with their application of a bilingual program at school.